A case of chronic cough due to sarcoidosis. (December 2022) - Low, Qin Jian; Misni, Mohd Nadzri Bin; Cheo, Seng Wee; Ng, Khai Lip; Muhammad, Noorul Afidza
Sarcoidosis is a multisystemic, chronic granulomatous disease of unknown aetiology that often affects the lungs. Diagnosis and treatment of sarcoidosis can be strenuous. Patients may be asymptomatic or experience cough, dyspnoea, fatigue, unintentional weight loss or night sweats. Computed tomography is valuable in the diagnosis of sarcoidosis. The typical histopathological lesion of sarcoidosis is granuloma without caseous necrosis in the involved organs. As tuberculosis is endemic in our region, clinicians should not forget this great mimicker. The cornerstone of treatment of sarcoidosis is corticosteroids but newer agents such as steroid-sparing agents and biological agents are available. We report a case of pulmonary sarcoidosis presenting with chronic cough.